The history of a surface in a single laser shot: from ultrafast carriers excitation to plasma emission, fading, and beyond - Carrasco-García, Irene María (UMA Editorial, 2021)
Laser ablation is currently a powerful tool in a wide range of aplications, concerning from removing several atoms from a surface to mechanical drilling. Despite all this applications are described by complex physico-chemical processes, they have in common the absorption of laser light into energy which heats the matter. If certain temperature is achieved by the heated sample, it can vaporized and even emit light, and its emission spectrum can be recorded. The development of ultrashort lasers have resulted in several advantages compared to laser with longer pulses, as the ablation dynamics processes can be separated in time. In this dissertation femtosecond pum-probe microscopy and LIBS are combined to relate the morphological dynamics induced during laser ablation and its further evolution into plasma emission, and describe a complete history of a surface in a single laser shot.
Keywords: Ablación láser - Tesis doctorales; Espectroscopía - Tesis doctorales; Femtosecond laser; Laser ablation; Pump-probe; Espectroscopia de emisión